2022
DOI: 10.33094/ijaefa.v14i2.662
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Omni-channel Value Perception and Customer Engagement on Customer Commitment, Mediated by Customer Trust

Abstract: This research aimed to analyse and reveal the influence of omni-channel perceived value and consumer engagement on customer trust and the implications thereof on customer commitment at BUKU IV banks in Jabodetabek, which are commercial banks based on business activities. The research employed a quantitative descriptive approach and a causal technique to a sample of 245 respondents. Structural equation modelling using the Lisrel Program was utilized as the method of data analysis. According to the research resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Impulsive consumers do not avoid urges associated with positive emotions such as happiness, satisfaction and relaxation. Nevertheless, these pleasant emotions are replaced by regret and even depression shortly after purchase (Cahaya, Mursitama, Hamsal, & Tjhin, 2022;Ploeger-Lyons & Butler, 2022;Sanderson et al, 2020;Vasudevan, Ping, & Wider, 2022). Individuals are supposed to benefit from unintended purchases buying is supposed to serve certain beneficial effects for the individuals, such as mood healing (changing negative effects and gaining short-term positive mood changes) and imagination and self-identity gestures.…”
Section: Consumers' Perspective Of Impulse Buyingmentioning
confidence: 99%
“…Impulsive consumers do not avoid urges associated with positive emotions such as happiness, satisfaction and relaxation. Nevertheless, these pleasant emotions are replaced by regret and even depression shortly after purchase (Cahaya, Mursitama, Hamsal, & Tjhin, 2022;Ploeger-Lyons & Butler, 2022;Sanderson et al, 2020;Vasudevan, Ping, & Wider, 2022). Individuals are supposed to benefit from unintended purchases buying is supposed to serve certain beneficial effects for the individuals, such as mood healing (changing negative effects and gaining short-term positive mood changes) and imagination and self-identity gestures.…”
Section: Consumers' Perspective Of Impulse Buyingmentioning
confidence: 99%
“…Cyr et al (2006) also found brand commitment to be a key factor in predicting continuance intention in the context of online financial transactions. Likewise, Cahaya et al (2023) found brand commitment had a positive effect on e-loyalty of e-banking. Many researchers found that brand commitment can differentiate those consumers who are brand loyal from others who repeat their purchase behaviors due to inertia or some habitual behavior (Dick and Basu 1994).…”
Section: Brand Commitmentmentioning
confidence: 95%
“…We employed quantitative methods to investigate various objective theories by examining relationships between variables [29,30]. The study focused on active students at Perbanas Institute who were at least 19 years old…”
Section: Methodsmentioning
confidence: 99%